ANALYSIS THE EFFECTS OF POVERTY, GENERAL ALLOCATION FUND AND ECONOMIC GROWTH TO HUMAN DEVELOPMENT INDEX (HDI) IN INDONESIA - Regina; Bahar Sinring; Muliyadi Hamid (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2020)
The aims of this research are to test and analyze the effects of poverty, general allocation fund (DAU) and economic growth to human development index (HDI) in Indonesia. The type of this research is quantitative research. This research used 33 provinces throughout Indonesia (exclude DKI Jakarta). Period of this research was during 2016-2018. Researcher did this research during September 2019-June 2020. The method used in this research is Pooled Data. This research used secondary data and the software of this research used Eviews. 8. The result found that (1) poverty has negatively significant effect (0.000) to human development index (HDI) in Indonesia, (2) general allocation fund has positively significant effect (0.000) to human development index (HDI) in Indonesia and (3) economic growth has no significant effect (0.676) and is negatively related to human development index (HDI) in Indonesia.